2016
DOI: 10.3892/ijmm.2016.2710
|View full text |Cite
|
Sign up to set email alerts
|

p43 induces IP-10 expression through the JAK-STAT signaling pathway in HMEC-1 cells

Abstract: p43 is a cofactor of aminoacyl-tRNA synthetase in mammals that effectively inhibits angiogenesis. However, the role of p43 in angiogenesis remains unclear. In the present study, we examined the effects of p43 on angiogenesis using human microvascular endothelial cells-1 (HMEC-1) cells as a model. Our microarray data showed that p43 regulated a number of cytokines, and the majoity of these are involved in the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) pathway. IP-10 was previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In addition, several other molecules pertinent to RA pathology are also regulated by JAK/STAT signaling. These include, IP-10, 99 TNFRSF12, a mediator of apoptosis 100 and IL-15. 101 In fact, Shenoy and colleagues, 102 showed that IL-15 regulated the Bcl-2 family proteins, Bim and Mcl-1 in T-cells.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In addition, several other molecules pertinent to RA pathology are also regulated by JAK/STAT signaling. These include, IP-10, 99 TNFRSF12, a mediator of apoptosis 100 and IL-15. 101 In fact, Shenoy and colleagues, 102 showed that IL-15 regulated the Bcl-2 family proteins, Bim and Mcl-1 in T-cells.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Whereas, the other cytokine trends indicate possible reversible action as variable expression patterns are viewed across time points. IP-10 and MIP-1b have known interactions and roles with the JAK/STAT protein pathway [24,25]. The JAK/STAT canonical pathway is a system of linked interactions involved in the phosphorylation of tyrosine residues in receptors creating active binding sites for proteins with Src-Homology (SH2) domains.…”
Section: Secreted Molecules Role In Signalling Pathways Controlling Nmentioning
confidence: 99%
“…On the other hand, high levels of AIMP1 activated c-Jun N-terminal kinase (JNK), which caused endothelial cells to undergo apoptosis. 54,62 The JAK-STAT signaling system automatically mediated the inhibitory effects of AIMP1 on angiogenesis. Also, it was found that AIMP1 is synthesized by pancreatic cells when the blood glucose level is less than 100 mg/dL.…”
Section: Catalytic Domain/new Additional Domainmentioning
confidence: 99%